Transient osteoporosis of the hip in a 17-year-old nonpregnant female: a case report - Abdirizak Abdullahi Sheikdon; Abdishakur Mohamud Ahmed; Omar Hassan Ahmed (Journal of Medical Case Reports)
Abstract Background Transient osteoporosis of the hip is a rare, self-limiting condition that typically affects middle-aged men and pregnant women in the third trimester. It is rarely observed in adolescents. Case report We present a unique case of transient osteoporosis of the hip in a 17-year-old Somali nonpregnant female who reported severe left hip pain and restricted mobility. Initial investigations revealed bone marrow edema on magnetic resonance imaging and deficiencies in phosphorus and magnesium. The patient was treated conservatively with bed rest, nutritional supplementation, bisphosphonates, and corticosteroids. This comprehensive approach led to significant improvement. At follow-up, the patient demonstrated complete resolution of symptoms and normalization of imaging findings. Conclusion This case underscores the importance of early diagnosis and targeted therapy in achieving full recovery from transient osteoporosis of the hip. Furthermore, it expands the demographic spectrum of transient osteoporosis of the hip, emphasizing its occurrence in nonpregnant adolescents.